Measurement of sound absorption properties of industrial organic waste material - (:unkn) unknown (KAUNAS UNIV TECHNOLOGY PRESS, 2008)
Sound absorption subject constitutes one of the major requirements for human comfort today. Therefore, sound absorption is needed in many area people use. Sound insulation requirements in industrial, in manufacturing environments, and in equipments, generating higher sound pressure, strives the need to develop more efficient and economical ways of producing absorption materials. Traditionally, economics of the research has enforced the researchers to focus on industrial nonwoven textile waste. Recently human hygiene and environmental protection has become another major requirement, resulting in more environmentally benign, natural materials to be used in such applications. Within this context, an industrial waste, developed during the processing of tea leaves was investigated for its sound absorption properties as opposed to a standard woven textile cloth and polyethylene and polyester based nonwoven fibers composed from textile waste. The material measurements implemented are based on the two-microphone transfer-function method according to ISO 10534-2 and ASTM E1050-98 international standards which is for horizontal mounting of orientation-sensitive materials; simulation of measurements on hanging ceilings, wall mountable. In this study, three different layers of tea-leaf-fiber (TLF) waste materials with and without backing of a single layer of woven textile cloth and sea urchin without backing were measured for their sound absorption properties. The results indicate that TLF sample without backing of 10mm thickness, exhibits a maximum sound absorption of 0.26 between 4000-6400Hz. Increasing the thickness of the sample, results in almost a linearly increasing trend in sound absorption, reaching to a peak value of 0.60 at 6400Hz. In order that backed TLF sample, increasing the thickness of the sample layer to 30mm yields, a sound absorption coefficient reaching to a maximum value of 0.90 at 2200Hz and a gradual decrease down to a level of 0.5 at 4900Hz. Sea urchin which is organic natural material has shown stable increase to 1600 Hz. Between 2400 - 6400 Hz however, reaction which is the peak value of sound absorption has been observed.
Keywords: acoustic measurement; material analysis; COMPOSITE